The Effectiveness of Using Social Media as A Promotional Tool for Dolomite Beach at Roxas Boulevard: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the effectiveness of using social media as a promotional tool for Dolomite Beach at Roxas Boulevard. Fifty (50) respondents, either residents or tourists, were selected using a quota sampling technique based on the survey questionnaire results. The study employed a descriptive research design, percentage, ranking, weighted mean, and survey questionnaire that used a Likert scale to show the effectiveness of social media in promoting tourist destinations, especially the Dolomite Beach at Roxas Boulevard. The study revealed that the effectiveness of social media was very high. Many social networking sites can be used to promote Dolomite Beach. This study also showed the effects of social media on the tourism industry, and one of these was to analyze performance and consumer satisfaction. This study recommended using Facebook, YouTube, TikTok, and Instagram as promotional tools for Dolomite Beach since this was the most used social media platform.